Indonesian Folktales in English: Media to Integrate Local Wisdom in EFL Classroom - Fadhli, Muhammad (Lingual Journal of Language and Culture, 2020)
Indonesia has a lot of folktales as one of the precious cultural heritages that must be preserved. A folktale provides cultural knowledge and moral lessons as one type of literary text. Using Indonesian folktales in English as teaching materials in the classroom of English as a Foreign Language (EFL) will contribute a great deal to the growth of the linguistic and cognitive skills, cultural understanding and moral values of students. This paper focuses on some of the benefits and considerations of using Indonesian traditional folktales from in English as a teaching aid in the EFL classroom.